Zaskakujące konsekwencje doświadczania lęków egzystencjalnych = Unexpected consequences of existential anxiety - Łukaszewski, Wiesław (1940- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The current article systematically presents major findings on how people deal with existential anxiety, especially, how they overcome the fear of dying. We present psychological buffers that help people to conquer their existential concerns, that is the cultural worldview, self-esteem, close relationships with other people, mood regulation, use of power, and focus on body appearance. We also discuss finding on fear of freedom losing and fear of loneliness.
Keywords: lęk egzystencjalny; światopogląd; samoocena; existential anxiety; cultural worldview; self-esteem